Reconfiguration of the ASEAN Power Map and Political Security: A Critical Review of Thailand’s Land Bridge - Zaskia Nurul Adilah; Imam Fadhil Nugraha (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
This study examines the predicted impact of the land bridge infrastructure development in Thailand on political security of regional organizations and the Southeast Asian region, highlighting the presence of numerous foreign investors in this project, which has the potential to reshape the power dynamics in Southeast Asia, while considering the implications of the dominance of each foreign-investing country, each with its own national interests. The land bridge could give rise to new challenges for ASEAN’s political security, particularly in upholding the long-cherished principle of centrality aimed at maintaining regional stability. It could also create a new arena for power struggles and intensify rivalry between the United States and China, both of which have expressed investment interest in the project. This study employs a descriptive qualitative approach using a scenario framework to systematically examine possibilities. The findings indicate that the land bridge could weaken ASEAN’s position, this research clarifies that the presence of foreign dominance through investment not only weakens ASEAN but also creates ASEAN’s dependence on various sectors depending on which investor nations succeed in dominating them.